Judging the probability of a contingent loss: An empirical study* - HARRISON, KENNETH E.; TOMASSINI, LAWRENCE A. (Contemporary Accounting Research, 1989)
This paper reports the results of research in which experienced auditors interpreted the criteria of Statement of Financial Accounting Standards No. 5 (SFAS 5): Accounting for Contingencies. The research focuses on two issues: (1) the nature and degree of consensus in the auditors' interpretations, and (2) the extent to which these interpretations depend upon the type of contingent loss. Forty‐five experienced auditors (managers, principals, and partners) from “Big 8” CPA firms responded to a research instrument that elicited their interpretation of SFAS 5 probability criteria. Our analysis focuses upon the thresholds between the “remote” and “reasonably possible” criteria and between the “reasonably possible” and “probable” criteria. Our results indicate: (1) threshold means of 0.16 and 0.68, respectively; (2) more auditor consensus for the first threshold than for the second; (3) the first threshold was significantly lower than indicated by previous research; and (4) the thresholds were generally not dependent upon the type of contingent loss.